2023
DOI: 10.3389/fsurg.2022.1031108
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of serum HMGB1 in patients with lower extremity arteriosclerosis obliterans after interventional vascular restenosis

Abstract: ObjectiveThis study explored the correlation between serum HMGB1 levels and postoperative vascular restenosis in patients with lower extremity arteriosclerosis obliterans (LEASO).MethodsA total of 362 patients LEASO who received vascular intervention were recruited in this study. Serum HMGB1 levels were measured by enzyme-linked immunosorbent assay. Logistic regression analysis was used to identify the influencing factors associated with vascular restenosis. The R procedure was used to create nomogram model. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…[3] Some studies demonstrated that methods to improve patients self-care ability, cognitive level of disease, and anxiety and depression can improve the postoperative quality of life of patients with peripheral arterial disease. [37,38] Our study showed similar results, with quality of life being a protective factor for postoperative frailty in patients undergoing PTA. Therefore, the continuous care of patients after discharge is very important.…”
Section: Discussionsupporting
confidence: 72%
“…[3] Some studies demonstrated that methods to improve patients self-care ability, cognitive level of disease, and anxiety and depression can improve the postoperative quality of life of patients with peripheral arterial disease. [37,38] Our study showed similar results, with quality of life being a protective factor for postoperative frailty in patients undergoing PTA. Therefore, the continuous care of patients after discharge is very important.…”
Section: Discussionsupporting
confidence: 72%